IMPLEMENTASI COOL JAPAN STRATEGY DI INDONESIA SEBAGAI KEPENTINGAN DAN NATION BRANDING JEPANG - Manik, Hiszkia Jonasz; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Cool Japan Strategy is an effort by Japan that utilizes its popular culture with the aim of revitalizing its economy, which experienced a recession in 2008. Indonesia is one of the target countries for Japan in implementing this strategy. Japan has carried out various implementations of the Cool Japan Strategy in Indonesia, such as cooperation, investment, and popular Japanese cultural events. Therefore, the researcher poses the question "How does Japan implement the Cool Japan Strategy in Indonesia?". To answer this question, the researcher adopts the perspective of Neoliberalism. This perspective is considered appropriate because Japan is a key actor in carrying out cooperation through the Cool Japan Strategy. This study utilizes the theory of National Interest and Competitive Identity to explain the Cool Japan Strategy. In conducting this research, the researcher employs a descriptive analysis method, which is used to describe and analyze the Cool Japan Strategy. The findings of this research indicate that Japan's interests in implementing the Cool Japan Strategy in Indonesia are not only economic interests but also nation branding. By capitalizing on the potential Indonesian market's interest in popular Japanese culture, Japan has successfully gained economic benefits and enhanced its global image. Keywords : Cool Japan, Cool Japan Strategy, Japanese culture, Nation Branding